Preferred Pore Orientation as a Complement to Anisotropy of Magnetic Susceptibility: A Case Study of Lava Flows From Batur Volcano, Bali, Indonesia - Desi Wulan Ndari, Nuresi Rantri; Suryanata, Putu Billy; Bijaksana, Satria; Dahrin, Darharta; Atarita, Fadhli Ramadhana; Pratama, Aditya; Hafidz, Abd; Fajar, Silvia Jannatul (Frontiers in Earth Science, 2020)
Anisotropy of magnetic susceptibility (AMS) analyses have been used widely in many applications that include studying lava flows. In this paper, we introduce an auxiliary parameter, i.e., preferred pore orientation, on the use of AMS for lava flow studies on the basaltic lava samples from Batur Volcano in Bali Indonesia. We also examine the effect of sample position in lava flow outcrop to the relationship between preferred pore orientation and AMS. The samples are subjected to petrographic analyses as well as to magnetic measurements and micro-computed tomography (μCT) imaging. Preferred pore orientations were obtained by quantified the long-axis of the vesicles from the images. The correlation was evaluated by measuring the angle between the maximum susceptibility axes and the preferred pore orientations. All samples show that the maximum susceptibility axes are parallel with the flow direction. Three out of six samples of two lava flows from the same eruption show a positive correlation between AMS and preferred pore orientation, where both parameters point to the northeast direction. A difference of sample position in the outcrop of lava flow was observed as a possible factor that influenced the results for the preferred pore orientations. Samples which were taken from the summit of the lava flow have pore orientation parallel to the lava flow direction. While samples which were taken from the foot slope of the lava flow have pore orientation perpendicular to the lava flow direction. This study provides further evidence that pore orientation might be positively correlated with the AMS.